2017
DOI: 10.1038/s41598-017-11207-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of influent C/N ratios and treatment technologies on integral biogas upgrading and pollutants removal from synthetic domestic sewage

Abstract: Three different treatment technologies, namely mono-algae culture, algal-bacterial culture, and algal-fungal culture, were applied to remove pollutants form synthetic domestic sewage and to remove CO2 from biogas in a photobioreactor. The effects of different initial influent C/N ratios on microalgal growth rates and pollutants removal efficiencies by the three microalgal cultures were investigated. The best biogas upgrading and synthetic domestic sewage pollutants removal effect was achieved in the algal-fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…Regarding the comparison between the digestate and BBM in terms of N removal, it was proven that A. protothecoides had the ability to assimilate nitrogen from the liquid digestate. The reduction of the N content in LD results from the process of assimilation of N by A. protothecoides cells, which is utilized for formation of proteins and nucleic acids or synthesis of phospholipids [22]. Similar results were obtained by Wang et al [23], who demonstrated that the total nitrogen content was reduced by 75.7%–82.5% by green microalgae Chlorella sp from digested dairy manure.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Regarding the comparison between the digestate and BBM in terms of N removal, it was proven that A. protothecoides had the ability to assimilate nitrogen from the liquid digestate. The reduction of the N content in LD results from the process of assimilation of N by A. protothecoides cells, which is utilized for formation of proteins and nucleic acids or synthesis of phospholipids [22]. Similar results were obtained by Wang et al [23], who demonstrated that the total nitrogen content was reduced by 75.7%–82.5% by green microalgae Chlorella sp from digested dairy manure.…”
Section: Discussionsupporting
confidence: 54%
“…Carbon is one of the most important elements utilized by algae and constituted 46%–50 % of dry microalgal biomass [22]. In the process of methane fermentation, the organic fraction of wastes is converted to CH 4 and CO 2 , which is dissolved into a liquid and generates a bicarbonate-carbonate buffer of an anaerobic liquid [30].…”
Section: Discussionmentioning
confidence: 99%
“…Potassium dihydrogen phosphate was applied as the phosphorus source. The influent C/N ratio was adjusted to 5:1 based on [ 30 ], as carbon and nitrogen are the vital nutrients and source of energy for the growth of microorganisms [ 29 ]. This ratio is important for the microorganisms to function at maximum efficiency, resulting in a stable anaerobic digestion process [ 28 , 29 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Samples from two inocula and anaerobic sludge representing different SRTs on Day 1,15,30,45,60,75,90,110,125, and 150, respectively, were analyzed for bacterial and archaeal community composition. The DNA of these samples was extracted using a FAST DNA Spin Kit for Soil (MP Biomedicals, Solon, OH, USA) according to the manufacturer's instructions.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…C is a basal element for microalgal growth and contributes up to about 50% of microalgal biomass (Xu, Wang, Sun, Zhao, & Hu, 2017). A previous study accessed the carbon mass balance and reported the assimilation into biomass as the main C removal pathway (Serejo et al, 2015).…”
Section: Nutrient Removalmentioning
confidence: 99%